Psikoedukasi dalam Meningkatkan Awareness pada Siswa Kelas 9B SMP N 45 Semarang - Siti Hikmah; Putri Asmara Dirgantari; Muhamad Krisna Bagus Virgiana; Alika Maezalati Usbah (Observasi : Jurnal Publikasi Ilmu Psikologi, 2025)
Adolescence is an important transitional stage in life involving physical development, psychological and sexual maturity, which often triggers curiosity about sexuality. Psychoeducation is designed to provide insight and raise awareness about sexual education. The implementation of this psychoeducation uses a Community Based Research approach. The results of this psychoeducation showed a positive impact in increasing students' understanding of sexual education.